Mechanisms driving the lactate switch in Chinese hamster ovary cells. Issue 8 (10th April 2018) - Hartley, Fiona; Walker, Tracy; Chung, Vicky; Morten, Karl
Abstract: The metabolism of Chinese Hamster Ovary (CHO) cells in a production environment has been extensively investigated. However, a key metabolic transition, the switch from lactate production to lactate consumption, remains enigmatic. Though commonly observed in CHO cultures, the mechanism(s) by which this metabolic shift is triggered is unknown. Despite this, efforts to control the switch have emerged due to the association of lactate consumption with improved cell growth and productivity. This review aims to consolidate current theories surrounding the lactate switch. The influence of pH, NAD + /NADH, pyruvate availability and mitochondrial function on lactate consumption are explored. A hypothesis based on the cellular redox state is put forward to explain the onset of lactate consumption. Various techniques implemented to control the lactate switch, including manipulation of the culture environment, genetic engineering, and cell line selection are also discussed. Abstract : A switch in lactate metabolism is frequently observed in a CHO cell production environment. Cultures transition from a lactate producing to a lactate consuming state, a feature which is associated with enhanced process performance. However, the molecular mechanism through which this switch is conferred remains enigmatic. This review uses existing data to argue that redox imbalance is the primary driver of this metabolic switch.